2014
DOI: 10.1155/2014/697103
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fecal Occult Blood Testing in Hospitalized Patients: Results of an Audit

Abstract: The present study suggests that FOBT results in hospitalized patients may have little beneficial impact on clinical management. Hospital laboratories may be better served in directing resources to other tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Previous studies describing the role of FOBT in the inpatient setting highlight the potential for FOBT to influence inappropriate clinical decision-making. [ 2 4 5 6 7 ] It has also been suggested that implementation of FOBT in the inpatient setting contributes to increased hospital length of stay and increased medical costs. [ 7 ] Yet, FOBT is commonly used in the acute hospital setting and its influence on clinical decision-making, patient management, length of stay, and medical costs have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies describing the role of FOBT in the inpatient setting highlight the potential for FOBT to influence inappropriate clinical decision-making. [ 2 4 5 6 7 ] It has also been suggested that implementation of FOBT in the inpatient setting contributes to increased hospital length of stay and increased medical costs. [ 7 ] Yet, FOBT is commonly used in the acute hospital setting and its influence on clinical decision-making, patient management, length of stay, and medical costs have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…6,13 Although there is data suggesting that advanced age and mean corpuscular volume may predict a positive endoscopic evaluation in patients with iron deficiency anemia, 14,15 there is limited data on which hospitalized patients with anemia and a positive fecal occult blood test (FOBT) have either positive findings on endoscopic evaluation or need endoscopic intervention. In this prospective study, we demonstrate that hospitalized patients with concern for occult GIB who have active malignancy and lower admission hemoglobin levels are more likely to have a positive source of GIB detected on endoscopic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…4 Because of its false positive results, inpatient guaiac testing commonly leads to negative endoscopic testing, 4,5 and has been shown to have little beneficial impact on inpatient clinical management. 6 In fact, despite endoscopic evaluation with upper esophagogastroduodenoscopy (EGD) and colonoscopy, the source of bleeding can remain undetected in patients with occult GIB in up to 52% of patients. 7 In such cases where initial endoscopic evaluation is unrevealing, current guidelines recommend consideration of further studies such as capsule endoscopy and enteroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, only 34% of hospitalized patients with a positive FOBT underwent further GI studies, with the majority of those patients (60%) receiving endoscopy before the results of the FOBT were known. 18 In another study of 201 FOBTs performed on hospitalized patients, those with negative results underwent further GI evaluation at a higher rate than those with positive results (41% vs 38%). 8 This aligns with a study that revealed the majority of patients suspected of having a GI bleed underwent endoscopic evaluation regardless of the FOBT result.…”
Section: Why Fobt Is Not Helpful For Evaluation Of Inpatients With Sumentioning
confidence: 98%